2004
DOI: 10.1007/s11663-004-0025-5
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion models for evaporation losses during electron-beam melting of alpha/beta-titanium alloys

Abstract: An analysis of the evaporation of aluminum during electron-beam melting (EBM) of alpha/beta-titanium alloys was performed. The analysis was based on the solution of the one-dimensional diffusion equation for the solute-concentration gradient in the melt pool subject to the flux boundary condition for the evaporation rate at the melt surface quantified using the Langmuir equation. The effect of process parameters and material coefficients (e.g., the diffusivity and solute activity in the melt) on predicted conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 14 publications
(58 reference statements)
0
21
0
Order By: Relevance
“…By using high power and high scanning speed, the cooling rate is fast enough to largely suppress α to α 2 phase transformation and promote a microstructure with the hard ordered B2 phase. On the other hand, a decreased scanning speed induces higher local superheat, thereby increasing the evaporation of aluminium 18 . Ge et al also reported the strong influence of energy input on Al evaporation for Ti-47Al-2Cr-2Nb powders 19 .…”
Section: ° the Ebm Processmentioning
confidence: 99%
“…By using high power and high scanning speed, the cooling rate is fast enough to largely suppress α to α 2 phase transformation and promote a microstructure with the hard ordered B2 phase. On the other hand, a decreased scanning speed induces higher local superheat, thereby increasing the evaporation of aluminium 18 . Ge et al also reported the strong influence of energy input on Al evaporation for Ti-47Al-2Cr-2Nb powders 19 .…”
Section: ° the Ebm Processmentioning
confidence: 99%
“…Based on the solution of the one-dimensional diffusion equation, several very recent investigations have provided an alternate method to describe the competition between diffu sion of solutes to the melt surface and subsequent evapora tion [14,17]. For example, Semiatin et al [17] used a solution from Carslaw and Jaeger [18] to estimate the total solute loss from a melt pool of depth d, surface area A, and initial solute composition Co (in kg/m 3 ), i.e., Total Flux = AdCo×…”
Section: Models For Ebchm Ingot Compositionmentioning
confidence: 99%
“…For example, Semiatin et al [17] used a solution from Carslaw and Jaeger [18] to estimate the total solute loss from a melt pool of depth d, surface area A, and initial solute composition Co (in kg/m 3 ), i.e., Total Flux = AdCo×…”
Section: Models For Ebchm Ingot Compositionmentioning
confidence: 99%
See 2 more Smart Citations